A quasi-experimental study to assess the effectiveness of structured teaching program regarding HIV-AIDS among the student of selected Jr. college in Aurangabad city - John , Joanna (Innovational: Journal of Nursing and Healthcare, 2024)
There are over 17.5 million people living with HIV/AIDS infection in the world today. India has the second highest number of people living with HIV/AIDS in the world. Therefore, a study was conducted to assess the effectiveness of structured teaching program regarding HIV-AIDS among the student of selected JR. College in Aurangabad city. Aim: To assess the pre-test knowledge regarding HIV-AIDS among the student of JR. college. To administer and find out the effectiveness of structured teaching program on HIV /AIDS among the student of JR. College. To find out association between the knowledge scores of HIV/AIDS with selected demographic variables. Methods: A Quasi Experimental study to assess the effectiveness of structured teaching program regarding HIV-AIDS among the student of selected JR. College in Aurangabad city. The sample consisted of 60 college students from Chate Jr. College Aurangabad, selected according to convenient sampling method and availability. Structured questionnaire was use to assess the knowledge regarding HIV-AIDS among college students. The pilot study was conducted and found feasible. Final study was carried out on 60 college students from Chate Jr. College. The data collected were analyzed with descriptive and inferential statistics using frequencies, percentage, mean, and mean percentage and standard deviation. Effect of structure teaching program (STP) was analyzed by paired t-test. Chi-square test was used to find the association with demographic variables. The pre test mean knowledge score of college students regarding HIV-AIDS was 15.733 and the mean post test knowledge score was 23.76. The mean percentage of college students regarding HIV-AIDS was 27.59% the mean post test percentage was 39.6%.